Essays in literary criticism - Villa, Jose Garcia (Quezon City, Philippines : Ateneo De Manila University Press, 2002)
The essays in this collection examine the evolution of Filipino fiction and poetry.
The Best Filipino Short Stories of 1927 -- The Best Filipino Short Stories of 1928 -- The Best Filipino Short Stories of 1929 -- The Best Filipino Short Stories of 1930 -- Again Graphic Leads -- The Best Poems of 1931 -- The Best Filipino Short Stories of 1932 -- Best Filipino Short Stories of 1933 [First Installment] -- The Best Filipino Short Stories of 1933 [Second Installment] -- Best Philippine Short Stories [of 1934] [First Installment] -- The Best Filipino Short Stories of 1934 [Second Installment] -- The Best Filipino Short Stories of 1935 -- Status of Criticism in the Philippines -- Form, Plot, Etc -- Reading and Appreciation -- Good, Better, and Best / Why Good Stories are Good -- The Best Filipino Short Stories of 1937 [First and Second Installments] -- The Best Filipino Short Stories and Poems of 1938 [First and Second Installments] -- The Best Filipino Short Stories for 1939 -- The Best Filipino Short Stories for 1940 [First and Second Installments] -- The Best Filipino Poems of 1939-1940 [First Installment] -- The Best Filipino Poems of 1939-1940 [Second Installment] -- Writing Short Stories in the Philippines -- Fifteen Literary Landmarks -- Our Intellectuals and Artists -- Poems for an Unhumble One -- The Status of Philippine Poetry [First Installment] -- The Status of Philippine Poetry [Second Installment] -- The Contemporary Short Story -- Fifteen Finest Filipino Short Stories, 1925-1936 -- The Rise of the Short Story in the Philippines -- Literary Criticism in the Philippines -- The Condition of Philippine Verse -- Villa's Letter of Defense -- "Villa Raps Faigao for Poetry Selections" -- "G-r-and Passion" -- Villa on Wilson's "Amphisbaenic Endings" -- Villa on Rafael Zulueta Da Costa -- "Villa on Philippine Poetry.".
Includes bibliographical references and index.
Keywords: PHILIPPINE LITERATURE